1989
DOI: 10.1007/bf00175583
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluation of acidic sulfate and nitrate in precipitation

Abstract: A simple method is presented and used to estimate the portions of SO 2 -and NO3-that contribute to the strong acidity in weekly precipitation samples collected at three NADP sites in the eastern United States. The method assumes that, in general, the difference between SO ] -and NH 2 represents acidic sulfate and the difference between NO3-and soil-derived materials (the sum of Ca 2 +, Mg 2 +, and K ÷ ) represents acidic nitrate. Acidic sulfate and nitrate are considered to be the predominant source of H + (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…This observation is in agreement with those made by other investigators [Berresheim et al, 1991;Huebert et al, 1996;Johansen et al, 2000;Naik et al, 1991;Savoie and Prospero, 1982;Sievering et al, 1990]. The reason is that in temperate regions and in the presence of H 2 SO 4 [Bassett and Seinfeld, 1984;Sisterson, 1989], HNO 3 evaporates from small particles and is subsequently deposited on large particles, which may be marine-or soil-derived. The PC analysis supports this phenomenon by demonstrating that NO 3 À in the coarse fraction correlates with the anthropogenic component.…”
Section: Nosupporting
confidence: 93%
“…This observation is in agreement with those made by other investigators [Berresheim et al, 1991;Huebert et al, 1996;Johansen et al, 2000;Naik et al, 1991;Savoie and Prospero, 1982;Sievering et al, 1990]. The reason is that in temperate regions and in the presence of H 2 SO 4 [Bassett and Seinfeld, 1984;Sisterson, 1989], HNO 3 evaporates from small particles and is subsequently deposited on large particles, which may be marine-or soil-derived. The PC analysis supports this phenomenon by demonstrating that NO 3 À in the coarse fraction correlates with the anthropogenic component.…”
Section: Nosupporting
confidence: 93%
“…These values are in close agreement with observations by other investigators [Berresheim et al, 1991; Davison et al, 1996; Ellis et al, 1993; Galloway et al, 1993; Harrison et al, 1996; Huebert et al, 1996; Li-Jones and Prospero, 1998; Savoie et al, 1989b] carried out in the same region, where the low concentration corresponds to a clean marine atmospheric situation and the high concentration is typical for a somewhat polluted air mass.Slightly more than half of the total NO•-(53%) is typically associated with the coarse particle fraction. This is in agreement with observations made by a series of investigators [Bassett andSeinfeld, 1984;Berresheim et al, 1991;Huebert et al, 1996;Savoie and Prospero, 1982;Sievering et al, 1990;Sisterson, 1989] that demonstrated that most NO•-is found in the supermicron mode associated with Na + and CI-, while most of the NSS-SO42-is contained in the submicron mode. This is in strong contrast with the behavior of other anthropogenic tracers; their content is considerably higher in the fine than in the coarse fraction' almost 3 times as much NSS-SO42-is present in the fine fraction, while the corresponding value of Zn is 2.6 and for Pb 2.5.…”
supporting
confidence: 93%
“…The three factors explain 99.7% of the total variance of all the data ( (Sisterson, 1989;Hov and Hjollo, 1994). The second factor (35.6% of the total variance) highlights the association of Na + , Cland Mg 2+ and then corresponds to the marine origin.…”
Section: Source and Processes Affecting The Rainwater Mineralization 155mentioning
confidence: 97%